Bioinspired Ultrasensitive Flexible Strain Sensors for Real-Time Wireless Detection of Liquid Leakage - Zhou, Weilong; Du, Yu; Chen, Yingying; Zhang, Congyuan; Ning, Xiaowei; Xie, Heng; Wu, Ting; Hu, Jinlian; Qu, Jinping (Nano-Micro Letters, 2024)
Liquid leakage of pipeline networks not only results in considerable resource wastage but also leads to environmental pollution and ecological imbalance. In response to this global issue, a bioinspired superhydrophobic thermoplastic polyurethane/carbon nanotubes/graphene nanosheets flexible strain sensor (TCGS) has been developed using a combination of micro-extrusion compression molding and surface modification for real-time wireless detection of liquid leakage. The TCGS utilizes the synergistic effects of Archimedean spiral crack arrays and micropores, which are inspired by the remarkable sensory capabilities of scorpions. This design achieves a sensitivity of 218.13 at a strain of 2%, which is an increase of 4300%. Additionally, it demonstrates exceptional durability by withstanding over 5000 usage cycles. The robust superhydrophobicity of the TCGS significantly enhances sensitivity and stability in detecting small-scale liquid leakage, enabling precise monitoring of liquid leakage across a wide range of sizes, velocities, and compositions while issuing prompt alerts. This provides critical early warnings for both industrial pipelines and potential liquid leakage scenarios in everyday life. The development and utilization of bioinspired ultrasensitive flexible strain sensors offer an innovative and effective solution for the early wireless detection of liquid leakage. Highlights: 1 Micro-extrusion compression molding and surface modification were proposed for the mass fabrication of a superhydrophobic thermoplastic polyurethane sensor (TCGS). 2 Inspired by scorpions, TCGS features Archimedean spiral crack arrays and micropores, achieving 218.13 sensitivity at 2% strain, a 4300% increase, and over 5000 usage cycles of durability. 3 The robust superhydrophobicity of TCGS improves sensitivity and stability for detecting small-scale liquid leakage, allowing precise monitoring across various sizes and compositions while providing early warnings in various scenarios.